A Study on the development and in-vivo evaluation of Exenatide Self-Emulsifying Drug Delivery System (SEDDS) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: The prevalence of diabetes has increased since 1980. This increased prevalence is responsible for a significant number of deaths. The advancement of different drug classes has been a practical solution, but the required pharmacological effect is not achieved due to the disadvantages of less bioavailability. One of the drugs, Exenatide, is being considered in this study. This current study aims to develop a Self-Emulsifying Drug Delivery System (SEDDS) for Exenatide to make it stable and increase its ability to permeate through the enterocytes to enhance its bioavailability and eventually improve blood glucose level status. The study further investigated the cytotoxicity of the whole system and compared the SEDDS effect on blood glucose level (BGL), stress biomarkers, and body weight with that of healthy rats, diabetic rats, and rats who were given Metformin.Materials and Methods: Exenatide is incorporated into the drug delivery system by ion-pairing method with sodium docusate (DOC) consisting of Cremophor-EL, Labrafil, Capmul-PG, and propylene glycol. The study used rats for the classification of groups and analysis between the groups to find out the effect on BGL status, effect on stress biomarkers, and effect on body weight. The authors have performed the characterization, release, and cytotoxic studies of SEDDS to show that the validation of Exenatide administration is feasible using a drug delivery system. Result: The study has found that SEDDS brings effective improvement in BGL status (P<0.001), prevents weight loss as compared to all other groups (P<0.001), and reduces stress biomarkers significantly (P<0.001). The authors also studied the permeation process and cytotoxicity of SEDDS to validate its usage. Conclusion: Combining the findings, SEDDS (Exenatide and DOC) can be considered to manage diabetes type 2 effectively. However, there is a need to conduct more animal experiments and clinical trials. Unlike any previous study, detailed and analytically significant findings have been conducted and discussed in this current study to improve the management of diabetes type 2